P3NEURO RECOGNISED AS A WORLD FEDERATION OF NEUROSURGICAL SOCIETIES TRAINING CENTRE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 2 December 2016 Centre for Neuroscience Services and Research (P3Neuro) and the Neuroscience Department of Hospital Universiti Sains Malaysia (HUSM) uses highend technology in its endeavour to improve health care, while teaching advanced medical sciences to its specialistsintraining in the field of clinical neurosciences.